2021
DOI: 10.1103/physrevresearch.3.013071
|View full text |Cite
|
Sign up to set email alerts
|

Exciton energy spectra in polyyne chains

Abstract: Recently, we have experimentally observed signatures of sharp exciton peaks in the photoluminescence spectra of bundles of monoatomic carbon chains stabilized by gold nanoparticles and deposited on a glass substrate [1]. Here, we estimate the characteristic energies of excitonic transitions in this complex quasi-one-dimensional nano-system with use of the variational method. We show that the characteristic energy scale for the experimentally observed excitonic fine structure is governed by the interplay betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Note that, by using the first‐principles calculations with me= 0.092m0 and me= 0.081m0 for a single carbon chain (Figure 4a), we deduce it's μ = 4.25 × 10 4 cm 2 V −1 s −1 and μ = 4.83 × 10 4 cm 2 V −1 s −1 in agreement with the earlier works. [ 30–31 ] Moreover, if we use the data with me= 0.012m0, [ 32 ] the electron mobility of a single carbon chain μ = 3.25 × 10 5 cm 2 V −1 s −1 which is larger than Artyukhov's result μ = 2.0 × 10 5 cm 2 V −1 s −1 , [ 32 ] graphene μ = 2.0 × 10 5 cm 2 V −1 s − 1, [ 33 ] single‐walled carbon nanotube (SWCNT) μ = 1.0 × 10 5 cm 2 V −1 s −1 , [ 34 ] and the intrinsic carrier mobility of silicene μ = 2.57 × 10 5 cm 2 V −1 s −1 . [ 35 ] Accordingly, the electron mobility of a single carbon chain is comparable to the mobility of graphene based on the theoretical results.…”
Section: Resultsmentioning
confidence: 99%
“…Note that, by using the first‐principles calculations with me= 0.092m0 and me= 0.081m0 for a single carbon chain (Figure 4a), we deduce it's μ = 4.25 × 10 4 cm 2 V −1 s −1 and μ = 4.83 × 10 4 cm 2 V −1 s −1 in agreement with the earlier works. [ 30–31 ] Moreover, if we use the data with me= 0.012m0, [ 32 ] the electron mobility of a single carbon chain μ = 3.25 × 10 5 cm 2 V −1 s −1 which is larger than Artyukhov's result μ = 2.0 × 10 5 cm 2 V −1 s −1 , [ 32 ] graphene μ = 2.0 × 10 5 cm 2 V −1 s − 1, [ 33 ] single‐walled carbon nanotube (SWCNT) μ = 1.0 × 10 5 cm 2 V −1 s −1 , [ 34 ] and the intrinsic carrier mobility of silicene μ = 2.57 × 10 5 cm 2 V −1 s −1 . [ 35 ] Accordingly, the electron mobility of a single carbon chain is comparable to the mobility of graphene based on the theoretical results.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the pair of polyynic carbyne N = 7 and cyclo [18]carbon has no matching absorption resonance peaks, although a small absorption resonance signal can be seen in the visible range (3.0711 eV) of carbyne N = 7 compared to other absorption peaks found at the UV range (5.2611 eV and 5.5073 eV). The faint absorption resonance signal of carbyne N = 7 can be attributed to excitonic transitions 16 . Moreover, previous experimental study of polyynic condensed-phase carbyne has found UV-vis absorption spectra signals at 5.21 eV and 5.40 eV for carbynes with lengths N = 8 − 12 14 .…”
Section: Td-dft: Electronic Properties and Optical Spectramentioning
confidence: 98%
“…Attempts to synthesize pristine carbyne have proven to be an arduous feat due to their high reactivity with increasing carbon chain bonds [21][22][23] . Synthetic carbynes have been found inside the multi-walled carbon nanotubes 11 and in a process called laser ablation in a liquid (LAL) [14][15][16] under high pressure 12 . Scalable synthesis of carbynes has shown to be possible inside a double-walled CNT, where the CNT provided a confined space for large quantities of carbynes to grow at very long lengths (as long as 6, 400 carbon atoms) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…18(k)). [129] Raman spectroscopy has been used in many studies to confirm the presence of confined LCC in CNTs, with the fingerprint Raman peak "C-mode" was found to appear in the range between 1790 cm −1 and 1860 cm −1 . [13,67,[130][131][132] Shi et al have confirmed that the C-mode frequency and length of short chains are linearly related, but for the long linear chains beyond ∼ 100 atoms confined in CNT, as shown with black dashed line in Fig.…”
Section: Optical Properties and Spectroscopic Characteristic: Light A...mentioning
confidence: 99%
“…The calculated transition energies of direct and indirect excitons as well as X + and X − trions are indicated with respect to the transition energy between uncorrelated electron and hole states. Reprinted with permission, [129] copyright ©2021 American Physical Society. All rights reserved.…”
Section: Optical Properties and Spectroscopic Characteristic: Light A...mentioning
confidence: 99%